Masjid sebagai Episentrum Dakwah: Transformasi Peran Masjid Agung Demak dari Era Kesultanan hingga Digital - Willis, Dzikri Cahya Putra; Rochanah, Rochanah (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the correlation between the historical function of the Great Mosque of Demak during the Demak Sultanate era and its management practices today. This study uses a qualitative descriptive aprproach method, data collection is carried out through direct observation, semi-structured interviews, and related literature studies. The theory used is the theory of contextual da'wah developed by Jalaluddin Rakhmat. The results of the study indicate that the Great Mosque of Demak plays a strategic role in the spread of Islam based on cultural acculturation and contextual da'wah from time to time. Challenges faced in the modern era include a decrease in the number of worshipers, lack of cooperation between administrators, and adaptation of digital technology. The strategies used involve strengthening management, empowering mosque youth, cross-sector cooperation, and utilizing social media. This study emphasizes the importance of maintaining the historical identity of a mosque while remaining adaptive to the dynamics of the times.